Bioethical approach to communication within phisician-patient relationship in pediatric icus and humanization - Garrafa, Volnei; Albuquerque, Maria Clara (Acta Bioethica, 2001)
In medical literature doctor/patient relation (D-P R.) continues to be the core issue of professional activity, despite the drawing back produced by techno-scientific breakthroughs. Bioethics has provided medical ethics with the possibility to think over the essential values of the profession, among which we underline the importance of communication in D-P R. Concomitant with bioethics contribution to the exercising of citizenry, society as a whole has demonstrated an ever-increasing interest in the notion of "good physician", what has resulted in a greater emphasis on the doctor/patient relationship issue, even as a way to healing. In this context, the paper is intended to be a reflective text in the light of bioethics on the communication within D-PR. setting. "Focus Group" technique has been used with parents, medical school students and intensivist physicians who participated as volunteers. During interviews and by means of questionnaires we tried to identify the effective participation of parents in doctor/patient dialogue. The interpretation of data obtained demonstrated the lack of communication in doctor/patient relationship and the need to value communication as a tool for humanization and ethical action.